Using Electronic Confederates for Experimental Research in Organizational Science. (January 2021) - Leavitt, Keith; Qiu, Feng; Shapiro, Debra L.
Organizational scholars frequently rely on experiments using human confederates or descriptions of vignette characters to study a range of phenomena. Although experiments with confederates allow for realism and rigor, human confederates have several critical limitations. We present a novel and efficient alternative: the use of responsive electronic confederates for manipulating constructs in dyadic, group, and team contexts. Specifically, we (a) define electronic confederates in an organizational research context, identify their optimal qualities, and review studies that have used them; (b) discuss challenges of utilizing human confederates and how electronic confederates may address these; (c) identify boundary conditions around using electronic confederates and, within these conditions, identify the many types of inquiry that can be aided by electronic confederates; (d) discuss validation strategies for electronic confederates, while increasing their believability to study participants; (e) provide materials for two versions of an adaptable research platform involving electronic confederates; and (f) identify future opportunities for developing novel tools for behavioral research. Our article thus provides a toolkit for organizational researchers that empowers them to utilize electronic confederates in their own research.